Perancangan Backend Portal Informasi Komite Olahraga Nasional Indonesia Denpasar Berbasis MVC - Hisyam Akmal Maulana; Pratomo Setiaji (Bulletin of Computer Science Research, 2026)
The rapid development of information technology has encouraged many organizations to implement website-based information systems to improve the effectiveness of data management and digital information distribution. KONI Denpasar, as an organization engaged in regional sports development, requires a backend system capable of supporting integrated information management because the previous data management process was still carried out conventionally and was not centralized. This condition caused the dissemination of organizational information to become less optimal and made administrative processes and long-term system development more difficult. Several previous studies have discussed the development of systems using the CodeIgniter framework; however, most of these studies focused on academic systems, administrative services, and sales systems, while research related to backend information portals for sports organizations remains limited. Therefore, this study aims to design and develop a website-based backend information portal for KONI Denpasar using the CodeIgniter 4 framework with the Model View Controller (MVC) architectural approach. The system development method applied in this research is the Systems Development Life Cycle (SDLC) using the Waterfall model, which consists of requirements analysis, system design, implementation, testing, and maintenance stages. The developed backend system includes features for managing news, event agendas, documentation galleries, user data, and administrator access rights to support more structured information management. System testing was conducted using the Black Box Testing method to ensure that all features functioned according to user requirements. The results of this study indicate that the backend information portal for KONI Denpasar was successfully developed and that all system features operated properly based on the testing results. This research contributes to the development of an integrated MVC-based backend information portal for sports organizations that can support information management in a more effective, structured, and easily maintainable manner in the future.